Sistem Informasi Bimbingan Belajar Berbasis Web Menggunakan Metode Waterfall - Kusuma, Karishma Tirta Jaya; Rizal, Khairul; Ariani, Fattya (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2024)
In the current digital era, online exams are becoming an increasingly popular alternative for measuring students' learning achievements, especially after the COVID-19 pandemic forced education and training institutions to switch to a distance learning system. This research aims to design a web-based tutoring information system at PT. Narapatih Inspiratama uses the Waterfall method. This system is designed to increase efficiency in the exam assessment and management process by reducing the need for physical space, operational costs, and providing flexibility for exam takers who cannot be physically present. The design results show that this system can facilitate supervisors in providing material and exams online, as well as providing alternative exams for participants who have problems attending class. With this system, it is hoped that it can improve the quality and efficiency of tutoring at PT. Narapatih Inspiratama